1999
DOI: 10.2134/jeq1999.00472425002800060005x
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Arsenic in Soils: I. Sorption of Arsenate and Arsenite by Four Australian Soils

Abstract: Ten soils varying widely in chemistry and mineralogy were used to examine the physical and chemical properties that influence As sorption processes in soils. The sorption of As was measured using a batch technique with Asv and AsIII concentrations added in background solutions of NaNO3 (0.003–0.3 mol L−1) and a range of pH values (2.0–8.5). The soils generally sorbed more Asv than AsIII at equivalent As concentrations. In general, highly oxidic soils sorbed three times more Asv than soils containing small amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
1
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 0 publications
12
98
1
6
Order By: Relevance
“…The investigations showed that As sorption was largely dependent on soil pH, and there was a general decrease in As (V) sorption as pH increase, while the proportion of As (III) sorbed by soil increased with increasing pH (Smith et al 1999). Smith et al (1999) observed that sorption by the soil ranged from approximately 0.80 of added As (III ) at low pH, to approximately 0.95 of added As (III) at pH 6 to 7. As stated previously, As (III) sorbed by the soil in this study was relatively higher at pH 6.76.…”
Section: Phytotoxic Effects Of Individual Metalsmentioning
confidence: 95%
See 1 more Smart Citation
“…The investigations showed that As sorption was largely dependent on soil pH, and there was a general decrease in As (V) sorption as pH increase, while the proportion of As (III) sorbed by soil increased with increasing pH (Smith et al 1999). Smith et al (1999) observed that sorption by the soil ranged from approximately 0.80 of added As (III ) at low pH, to approximately 0.95 of added As (III) at pH 6 to 7. As stated previously, As (III) sorbed by the soil in this study was relatively higher at pH 6.76.…”
Section: Phytotoxic Effects Of Individual Metalsmentioning
confidence: 95%
“…Arsenate [As (V) ] and arsenite [As (III) ] are the primary forms of inorganic As in soils, and As (III) is the most toxic, soluble, and mobile species found in the environment (Masscheleyn et al 1991, Smith et al 1999). The investigations showed that As sorption was largely dependent on soil pH, and there was a general decrease in As (V) sorption as pH increase, while the proportion of As (III) sorbed by soil increased with increasing pH (Smith et al 1999). Smith et al (1999) observed that sorption by the soil ranged from approximately 0.80 of added As (III ) at low pH, to approximately 0.95 of added As (III) at pH 6 to 7.…”
Section: Phytotoxic Effects Of Individual Metalsmentioning
confidence: 99%
“…In aerobic conditions, the desorption of As(V) by the soil increases along with pH as a consequence of the increased negative charges of soil colloids [3,6]. Nevertheless, a decrease in pH, for example, in the rhizosphere, may result in the dissolution of Fe and Al oxides and hydroxides, with the consequent codissolution of As bonded to this fraction [7].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of soil (iii) Fluvisols: The highest total extractable As contents in both seasons because of lack of sorption sites and/or low content of organic matter in this soil were observed in this case. In soils with low content of oxide minerals was observed three times lower sorption of arsenate compared to highly oxidic soils (Smith et al 1999). Almost all the arsenic present in extracts was DMA (98%) without any changes between growing seasons.…”
Section: Soilsmentioning
confidence: 87%